PSIKODIAGNOSTIK DAN KESULITAN BELAJAR SISWA BIDANG PENDIDIKAN AGAMA ISLAM DI SOMBOONSARD SCHOOL, THAILAND - Galuh Candra Puspita Sari; Eva Latipah (Jurnal Pendidikan Agama Islam, 2016)
Psychodiagnostics is a research about human’s attitude and behaviour. Psychodiagnostics was used in order to obtain information about students’ learning dissability in Somboonsard School, Nathawee, Songkhla, Thailand, where it is located in muslim minority area. The result of this research showed that some students’ learning dissabilities were found. Some were simple kind of learning dissabilities, such as reading dissability and memorizing dissability. Some were complicated kind of learning dissabilities, such as dyslexia, slow learner, and emotional and behaviour disorders. From the diagnosis, people willbe able to find the best prognosis/solution to solve the problem of learning dissability. For example, reading and writing guidance, reading Al-Qur’an guidance, learning guidance, tasks giving, intensive individual counselling service and special guidance from psychologist. They also did preventive service in creating a corporation with supports.